Cytotoxicity of fluconazole on canine dental pulp-derived stem cells - Paulo Henrique Utumi; Letícia Fracaro; Felipe Yukio Ishikawa Fragoso; Dayane Mayumi Miyasaki; Paula Joly dos Santos; Lidiane Maria Boldrini-Leite; Paulo Roberto Slud Brofman; José Ademar Villanova, Jr; Alexandra Cristina Senegaglia (Elsevier, 2020)
Objective: In order to use fluconazole as an antifungal in cell cultures, we evaluated its possible cytotoxic effects and its influence on the proliferation and viability of canine dental pulp-derived stem cells (cDPSCs). Methods: Samples from permanent canine teeth were placed in a sterile tube with IMDM, penicillin-streptomycin, sodium heparin, and different concentrations of fluconazole. Dental pulp was digested (collagenase type II) and expanded in vitro. After 12 days of culture, enzymatic dissociation of the cDPSCs was performed to quantify, differentiate, and characterize the cells. Cytotoxicity was evaluated based on cell viability in response to fluconazole treatment using the 7-AAD dye. Results: Characterization of the cDPSCs revealed that fluconazole had no influence on the immunophenotypic characteristics and differentiation of these cells. Cell proliferation assay revealed that fluconazole did not significantly interfere with the replication capacity of the cDPSCs. Cytotoxicity analysis revealed a loss of cell viability as the fluconazole concentration increased. Although there was an increase in cell mortality, the number of dead cells remained low. Though the higher concentration of fluconazole (240 μg/mL) resulted in a higher number of non-viable cells, it remained safe for use. Conclusion: To prevent fungal contamination that causes a loss of samples during expansion of cDPSCs and to maintain minimal cell toxicity, we suggest adding 120 μg/mL of fluconazole to the teeth collection medium and cDPSCs culture.